Development of Rapid Immuno-based Nanosensors for the Detection of Pathogenic Bacteria in Poultry Processing Plants. (2017) - Alamer, Saleh; Chinnappan, Raja; Zourob, Mohammed
Abstract: Foodborne diseases is a major public health concern and costs billions of dollars losses every year. For example, 93.8 million cases of gastroenteritis reported in Europe, United States, South America and Asia. Different methods depending on various scientific principles are used for detection of pathogenic bacteria relating foodborne diseases, conventional methods including culture-depending methods, microscopic, PCR, serological and biochemical methods are still used but majority of this methods suffers from a number of disadvantages includes long time-analysis, high cost, limited sensitivity and lab-based. Therefore, there is an urgent need for development of rapid screening assays for field applications with high sensitivity. In this study, we developed colorimetric immuno-sensor was developed and evaluated as a novel rapid detection nanosensing platform for the detection of foodborne pathogens such as Salmonella Typhimurium, Salmonella Enteritidis, Staphylococcus Aureus and Campylobacter Jejuni. The sensing platform composed of cotton swab and nanoparticles. Cotton swaps were functionalized with general or specific recognition receptors for collecting and pre-concentration of bacteria from the surfaces. Then the cotton swab was dipped in a developing solution to indicate the presence of specific bacteria. The developing solution has a cocktail of different coloured nanospheres conjugated with different recognition receptors for the various bacteria analytes was used to generate the different colours. The nanosensor was used for testing the bacteria on different surfaces mimicking the poultry processing units such as glass slides, stainless steel and chicken meat.